FDI-led growth models - Woodgate, Ryan (Berlin School of Economics and Law, Institute for International Political Economy Berlin, 2022)
This paper develops two Sraffian supermultiplier models of two different kinds of economies that are dependent upon foreign direct investment (FDI): the
10419/266642
Keywords: Graue Literatur; Foreign direct investment; growth model; multinational corporation; tax haven